Can't We Write a Little Script for This? Managing Serials Data and xISSN. - Beccaria, Mike; Tennant, Roy; Traub, Adam; Romaine, Sion (Serials Librarian)
The Online Computer Library Center's xISSN Web service is an application program interface (API) that enables libraries to retrieve serials metadata from WorldCat in a parsable form. The service allows libraries to use a script language to 'mash' or combine the metadata with local serials holdings information, thereby enhancing their Web-based catalogs, databases, or A-Z lists. This tactics session provided an overview of the xISSN Web service, and provided two examples of how xISSN metadata has been used with scripts to improve the functionality of academic library A-Z lists.